ISSUES OF IMPROVING THE ACTIVITIES OF THE CHAMBER OF ADVOCATES OF THE REPUBLIC OF UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the legal status of the institute of the Bar in the Republic of Uzbekistan, the mechanisms of the Chamber of Advocates' activities, and the issues of their improvement. The independence, institutional potential of the Chamber of Advocates, its role in protecting the professional rights of lawyers, and its adaptation to international experience are scientifically, theoretically, and practically covered. Also, proposals and recommendations are put forward for the development of the bar system.